SCHÖPFUNGSTERMINOLOGIE IN DER SEPTUAGINTA VON JESAJA 44,24-45,25 - Oláh, Zoltán (Sacra scripta, 2009)
The present paper tries to present the way the Septuagint of Isaiah translated the creation terminology of the Hebrew Bible. In Is 44,24–45,25 there is a high concentration of verbs that belongs to the creation terminology. This pericope comprises the major verb of creation ar'B', which also occurs 6 times in the first creation account of the Hebrew Bible, just like in the above indicated pericope. The first part of the paper analyses the creation terminology and its problems according to the Masoretic Text. The second part focuses on the Greek creation terminology, as it is found in the Is-LXX 44,24–45,25. Sur¬prisingly the Greek text of Isaiah does not have yet the specific creation terminology found in later Greek texts of Wisdom, Sirach and Maccabees